ASSESSING CULTURAL CONTENT IN ENGLISH TEXTBOOK FOR HIGH SCHOOL GRADE 12 STUDENTS: A CASE STUDY - Ardnyananisari, Fannysa Dyah; Ratri, Devinta Puspita (University of Kuningan, 2024)
This research analyzes the cultural content presentation in the textbook